2019
DOI: 10.1167/iovs.18-24799
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Children Exhibit Evident Compensatory Role of Internal Astigmatism in Distribution of Astigmatism: The Nanjing Eye Study

Abstract: PURPOSE. To determine the prevalence and associated risk factors for total, corneal, and residual astigmatism and to evaluate the relations between components of astigmatism in Chinese preschool children. METHODS. In the population-based, cross-sectional Nanjing Eye Study, children were measured for noncycloplegic refractive error using an autorefractor and for biometric parameters using an optical low-coherent reflectometry. Data from right eyes were analyzed to calculate the prevalence of astigmatism using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
2
17
2
Order By: Relevance
“…When compared with the Shandong Children Eye Study, which was also carried out among Chinese children, the prevalence in this study was lower [15]. Our previous study also showed the TA prevalence was lower than that from The Shandong Children Eye Study [20,28]. Few studies revealed the prevalence of vectorial aniso-TA.…”
Section: Discussioncontrasting
confidence: 50%
“…When compared with the Shandong Children Eye Study, which was also carried out among Chinese children, the prevalence in this study was lower [15]. Our previous study also showed the TA prevalence was lower than that from The Shandong Children Eye Study [20,28]. Few studies revealed the prevalence of vectorial aniso-TA.…”
Section: Discussioncontrasting
confidence: 50%
“…The NES is an ongoing population-based open cohort study, designed to longitudinally observe the onset and progression of childhood ocular diseases in eastern China [9,[12][13][14][15]. The study was approved by the institutional review board in The First Affiliated Hospital with Nanjing Medical University and was conducted in accordance with the tenets of the Declaration of Helsinki.…”
Section: Study Populationmentioning
confidence: 99%
“…Previous studies have found many factors associated with astigmatism including high risk genes, eyelid pressure, extraocular muscle tension, gestational age, birth weight, nutrition [1], ethnicity, spherical equivalent refractive error, maternal smoking during pregnancy [2], accommodative convergence/accommodation ratio (AC/A) [3], age, education, ametropia [4], the axial length-corneal radius ratio (AL/CR) [5], delivery mode [6], socio-economically deprivation [7] and iris color [8]. In a recent paper on 48-60-month-old Chinese children [9], we reported the prevalence of the components of astigmatism, described the difference between corneal astigmatism (CA) and anterior corneal astigmatism (ACA), and demonstrated the compensatory role of internal astigmatism (IA) in reducing ACA. In addition, we evaluated the role of age, gender, and AL/CR on the components of astigmatism.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive questionnaire was distributed to legal guardians of each child. The examining procedures and content of the questionnaire have been described in detail previously [20,21]. The Apgar score is the most widely recognized index used to report the health status of a newborn [22], which is usually obtained by evaluating the following 5 items: appearance (color), pulse (heart rate), grimace response (re exes), activity (muscle tone) and respiration (breathing rate and effort) at one, ve and ten minutes after delivery, with the range being 0-10 [23].…”
Section: Ocular Examinations and Questionnairesmentioning
confidence: 99%